Multibeam bathymetry raw data (Kongsberg EM 124 entire dataset) of RV MARIA S. MERIAN during cruise MSM138 - Jan Oliver Eisermann; Henriette Wilckens; Sebastian Krastel; Gabriele Uenzelmann-Neben; Anne-Cathrin Wölfl (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM138 using a Kongsberg EM 124 multibeam echosounder. The expedition took place during 2025-06-16 – 2025-07-22 from Reykjavik (Iceland) to Reykjavik (Iceland) in the North Atlantic. The aim of MSM138 has been to study variations in flow paths and intensities of Iceland Strait Overflow Water (ISOW) in response to a) uplift/subsidence of the Greenland Scotland Ridge (GSR), and b) climate variability. An additional aim was the compilation of an input dataset for the numerical simulation of the overflow. Data were recorded within the Danish EEZ (Faeroe) and the Icelandic EEZ. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, provision of the data is supported by the DAM Project Underway Research Data and published according to the FAIR principles.